Axexe: a rite of passage. - Manzochi, Helmy Mansur (Revista do Museu de Arqueologia e Etnologia, 1995)
We describe the Axexê ceremony, observed at the terreiro de Candomblé, “Ilê Olorum Warn Be”, in 1991, in São Paulo”. It is celebrated when an important person of the community dies. To the African people, death doesn’t mean a total extintion, but a change of dimension and status, to reach the “ancestral condition”.